(3cdjGJ TQM fajSjs - (3fajS Hf YhV Hf Mcje GdcQeGfj, HQgGf GdOjf , HYO (B841 (3g` s ((3Ydj CcHQ GdWHjH GdSGdjGfjs)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdMHQ GdcGed YdGA GdOjf Ydj Hf CHj GdMRe GdbQTj GdeJWHH UjZI JaYd ggfG ddeHGdZI eKd JbOS hJeLO, bO QJHJ gPG GdcJGH Ydi CQHYI afhf(B: (3GdJQJjH hVY cd TjA aj eQJHJg hGdeUfa QMeg Gddg LYd hVY Gdafhf GdCQHYIs
(3BNQgG (B:s
(3heYfGg aj dZI GdYLe GdPj jbGhe GdSe cd eG jMaR UMI GdQhM hbhJg djJecf ef OaY VQQ GdSehe HNGUjI ajg hHYV Gdbhe jNJUQhf GdJQjGb HGdeQcHGJ ecf GdeUfhYGJ Je GdHGH GdChds
(3JHUQI GdYfhGf (B:s
(3TQM GdehLR aj GdWH dGHf GdfajSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8/44s
(3cTa GdXfhf (B2\1899s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs